Characterization of superoxide dismutases in the Antarctic scallop Adamussium colbecki. - Mattiuzzo E.; Cattalini F.; IRATO, PAOLA; FERRO, DIANA; TALLANDINI, LAURA; BALLARIN, LORIANO; SANTOVITO, GIANFRANCO (2014)
Superoxide dismutases (SODs) are considered the most important and ubiquitous antioxidant enzymes, involved in cellular antioxidant defenses, maintaining the redox homeostasis during the aerobic cell metabolism. Moreover, SODs are also closely involved in the innate immune response of animals, as evidenced by the rapid modulation of transcription during challenges with endotoxins, bacteria or viruses. During infection, the host often uses reactive oxygen species (ROS) to react to pathogenic invaders via phagocytosis. However, excess ROS generated during the respiratory burst may also be harmful to the host, that use the antioxidant machinery to maintain low ROS concentration in the cytoplasm. Antarctic species are characterized by a large number of special physiological features that allow the life in the extreme environment. First of all, low temperature and salt concentration are physicochemical conditions that increase oxygen solubility and, consequently, the rate of ROS formation. For this reason, a finely modulated antioxidant system is essential to prevent macromolecules oxidation that could result in DNA damage, loss of membrane integrity and changes of protein activities. Despite numerous previous studies on SODs from aquatic animals, only few data are available for the SODs of Antarctic mollusks. In the present work, we studied the Antarctic scallop Adamussium colbecki, a bivalve mollusk widely distributed in the Antarctic Ocean; for the first time we characterized the gene structure and expression of Adamussium SOD. Specimens were sampled in the Ross Sea (Terra Nova Bay, 74°42’S, 164°7’E) during the XXI Italian Antarctic Expedition. Partial cDNA sequences of Cu,Zn SOD and Mn SOD were obtained from gonadic tissue by RT-PCR and TA-cloning. The obtained nucleotide and deduced amino acid sequences were compared with those of orthologous genes already available in GenBank and the protein phylogenies were reconstructed. We also studied the gene transcription and enzyme activity in various organs and tissues, ...